2020
DOI: 10.1126/sciadv.aay6515
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear actin regulates inducible transcription by enhancing RNA polymerase II clustering

Abstract: Gene expression in response to stimuli underlies many fundamental processes. However, how transcription is regulated under these scenarios is largely unknown. Here, we find a previously unknown role of nuclear actin in transcriptional regulation. The RNA-seq data reveal that nuclear actin is required for the serum-induced transcriptional program. Using super-resolution imaging, we found a remarkable enhancement of RNA polymerase II (Pol II) clustering upon serum stimulation, and this enhancement requires nucle… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 58 publications
3
69
0
Order By: Relevance
“…There is, however, growing evidence that nuclear F-actin assembly plays important roles in transcription [ 91 ], mitosis [ 92 ], DNA replication [ 93 ], DNA repair [ 94 ] and chromatin regulation [ 95 ]. Nuclear F-actin filament formation has been observed following DNA repair response (DDR) activation, caused by telomere uncapping, treatment with genotoxic drugs or UV radiation.…”
Section: Contributing Factors To Nuclear Mechanicsmentioning
confidence: 99%
“…There is, however, growing evidence that nuclear F-actin assembly plays important roles in transcription [ 91 ], mitosis [ 92 ], DNA replication [ 93 ], DNA repair [ 94 ] and chromatin regulation [ 95 ]. Nuclear F-actin filament formation has been observed following DNA repair response (DDR) activation, caused by telomere uncapping, treatment with genotoxic drugs or UV radiation.…”
Section: Contributing Factors To Nuclear Mechanicsmentioning
confidence: 99%
“…Emergence of tools to specifically study actin filaments in the nucleus using specific reporters with nuclear localization signals as well as the presence of filament regulators such as WASp and Arp2/3 in the nucleus have reignited interest in this field. A role for nuclear actin filaments has been described in (1) homologous repair of heterochromatic double strand breaks in Drosophila oocyte where actin nucleation via Arp2/3 generate tracks for myosins to transport heterochromatic double-strand break to the nuclear lamina ( 128 , 129 ), (2) regulating gene expression following serum starvation via N-WASp/RNA polymerase II interactions ( 130 ) and (3) in regulating the expression of key cytokines downstream of T cell receptor engagement ( 126 , 131 ).…”
Section: Malignancies In Pid Patientsmentioning
confidence: 99%
“…It has been shown that remodelling of the actin cytoskeleton is a major pathway involved in TGFβ1 signalling 30 . Actin is constantly shuttled between the cytoplasm and the nucleus, where it has been shown to associate with the chromatin remodelling complex and POL2 to enhance transcriptional activity 31-33 . As transcriptional regulation were among the most enriched GO term in TGFβ1-damaged EPCs, we hypothesized that ph-EZH2 may facilitate the transcriptional process of the pro-fibrotic genes through POL2 and nuclear actin.…”
Section: Mainmentioning
confidence: 99%